Terapia dociskiem w zaburzeniach przetwarzania sensorycznego = Clamp therapy in disorders of sensory processing - Katarzyna Strojek; Agnieszka Radzimińska; Urszula Kaźmierczak; Irena Bułatowicz; Aleksander Goch; Walery Zukow (Kazimierz Wielki University, 2015)
Strojek Katarzyna, Radzimińska Agnieszka, Kaźmierczak Urszula, Bułatowicz Irena, Goch Aleksander, Zukow Walery. Terapia dociskiem w zaburzeniach przetwarzania sensorycznego = Clamp therapy in disorders of sensory processing. Journal of Education, Health and Sport. 2015;5(11):698-704. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.42113 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A698-704 http://pbn.nauka.gov.pl/works/686133 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015.   Terapia dociskiem w zaburzeniach przetwarzania sensorycznego Clamp therapy in disorders of sensory processing   Katarzyna Strojek1, Agnieszka Radzimińska1, Urszula Kaźmierczak1, Irena Bułatowicz1, Aleksander Goch1, Walery Zukow2   1. Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska 2. Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska   Adres do korespondencji: dr n. med. Agnieszka Radzimińska Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy Katedra Fizjoterapii ul. Techników 3, Bydgoszcz e-mail: agnieszka.radziminska@gmail.com     Streszczenie   Zaburzenie przetwarzania sensorycznego (SPD - Sensory Processing Disorder) tzw. dysfunkcja integracji sensorycznej ma miejsce, gdy mózg nieprawidłowo analizuje bodźce docierające z ciała lub środowiska zewnętrznego. Metoda integracji sensorycznej to jedna z ważniejszych metod wykorzystywanych w pracy z dziećmi z zaburzeniami w rozwoju. W pierwszej kolejności kierowana jest do dzieci z trudnościami w uczeniu się. Może być także wykorzystana jako forma profilaktyki ewentualnych trudności w uczeniu się oraz stymulacja rozwoju dzieci prawidłowo rozwijających się. Głównym zadaniem stymulacji układu dotykowego stosowanej w terapii SI (SI - Sensory Integration) jest dostarczanie dziecku przez terapeutę różnych bodźców dotykowych na określonych częściach ciała. Dziecko odpowiada na pytania terapeuty dotyczące struktury bodźca zewnętrznego, lokalizacji ciała, nazywa doznania odbierane w trakcie i po zastosowaniu bodźca. Układ dotykowy ma silne powiązanie z układem westybularnym. Dziecko z dysfunkcją przedsionkową może nie czuć się bezpiecznie, zarówno fizycznie, jak i emocjonalnie. W skład terapii dociskowej, stosowanej w metodzie integracji sensorycznej, wchodzi masaż dociskowy oraz stosowanie kamizelek i kołder dociążających. Masaż dociskowy poprawia czucie powierzchowne i głębokie, przyczyniając się do zwiększenia bezpieczeństwa emocjonalnego dziecka, ponieważ pomaga dziecku zorientować się, w jaki położeniu znajdują się jego poszczególne części ciała.   Summary   Sensory processing disorder occurs when the brain incorrectly analyzes the stimuli coming from the body or the external environment. The method of sensory integration is one of the most important methods used in working with children with development disorders. The first is directed to children with learning difficulties. It can also be used as a form of prevention possible difficulties in learning and stimulate the development of typically developing children. The main purpose of stimulation of the touch sensors used in sensory therapy integration is to provide a child by the therapist different tactile stimuli in certain parts of the body. The child responds to the questions of the therapist on the structure of an external stimulus, the location of the body, called sensations received during and after application of the stimulus. Touch system is a strong link in the vestibular system. A child with vestibular dysfunction can not feel safe, both physically and emotionally. The treatment of the pressure used in the method of sensory integration comes the pressure massage and the use of life jackets and ballasted quilts. Pressure massage improves the feeling of superficial and deep, contributing to the child's emotional security, because it helps the child get an idea of what position are its individual parts of the body.   Słowa kluczowe: terapia dociskiem, zaburzenia przetwarzania sensorycznego. Keywords: pressure therapy, disorders of sensory processing.